CFTR dictates monocyte adhesion by facilitating integrin clustering but not activation - Doulathunnisa Ahamed Younis; Mason Marosvari; Wei Liu; Sunitha Pulikkot; Ziming Cao; Beiyan Zhou; Anthony T. Vella; Sara McArdle; Liang Hu; Yunfeng Chen; Wenqi Gan; Ji Yu; et al. (Proceedings of the National Academy of Sciences, 2025)
Monocytes are critical in controlling tissue infections and inflammation. Monocyte dysfunction contributes to the inflammatory pathogenesis of cystic fibrosis (CF) caused by CF transmembrane conductance regulator (CFTR) mutations, making CF a clinically relevant disease model for studying the contribution of monocytes to inflammation. Although CF monocytes exhibited adhesion defects, the precise mechanism is unclear. Herein, superresolution microscopy showed that an integrin clustering but not an integrin activation defect determines the adhesion defect in CFTR-deficient monocytes, challenging the existing paradigm emphasizing an integrin activation defect in CF patient monocytes. We further found that the clustering defect is accompanied by defects in CORO1A membrane recruitment, actin cortex formation, and CORO1A engagement with integrins. Complementing canonical studies of leukocyte adhesion focusing on integrin activation, we highlight the importance of integrin clustering in cell adhesion and report that integrin clustering and activation are distinctly regulated, warranting further investigation for selective targeting in therapeutic strategy design involving leukocyte-dependent inflammation.